Education and citizen participation as strategic tools in the conservation of cultural heritage in Spain: a review of the current state of national and regional legislation - López-Mera, Alejandra; de Castro-Martín, Pablo; Fontal-Merillas, Olaia (Arte, Individuo y Sociedad, 2025)
This article reviews national and regional legislation in Spain concerning cultural heritage, with a particular focus on provisions related to the educational sphere and citizen participation. Through a detailed analysis, it examines legislative developments and processes that recognize these dimensions as strategic tools to ensure the conservation of heritage and the transmission of its cultural value and historical legacy to present and future generations. The study reveals that, although some recent laws have begun to incorporate explicit references to education and citizen participation, other regulations still overlook these aspects. This disparity highlights a significant gap in the implementation of educational programs and projects—both in formal and non-formal contexts—which considerably limits the success of initiatives aimed at cultural preservation through education. In response to this situation, the article proposes recommendations for future legislative updates, grounded in research that supports the inclusion of concrete measures. It advocates for the promotion of inclusive citizen participation that encompasses all age groups and environments, placing education at the core of efforts to safeguard and enhance cultural heritage.